STRATEGI ADAPTASI DESA WISATA PONGGOK TERHADAP PANDEMIC COVID-19 - titi pratiwi; Bagus Ramadhan (Jurnal Pariwisata Indonesia, 2023)
The Covid-19 pandemic has had an impact on the tourism sector, the condition of the tourism sector is currently weakening along with the ongoing Coronavirus outbreak, and even now the whole of Indonesia is experiencing a decline in the number of tourist visitors. Ponggok Village is one of the tourist villages which has been affected by the Covid-19 pandemic outbreak where the number of visitors to tourist objects in the village has decreased during the pandemic.The research approach used in this study is descriptive- qualitative. The method used to achieve the research objective is to determine the influence and strategies for handling the Covid-19 pandemic in the Ponggok tourist village. Data collection methods are observation, interviews, and document analysis, such as data reduction and drawing conclusions.The results of this study are that the Covid-19 pandemic affects community and tourism activities. The Covid-19 pandemic has disrupted the condition of the tourism sector, decreased the number of visits and income for both villages and tourism object management revenue, and postponed village and tourism activity programs. The handling strategy carried out by the village government is reviewing plans, modifying tourism area policies, collaborating, and approaching the community to build a spirit of cooperation. Handling strategies carried out by tourism object managers are minimizing expenses, utilizing funds, managing funds, collaborating, maximizing services, developing or implementing health protocols, developing and transferring markets, and evaluating. While the strategy carried out by stakeholders and MSMEs is to increase cooperation between managers and business actors, change and transfer business or sales systems, implement a consignment system, and transfer jobs.